Identification and utilization of flexibility in non-residential buildings. (September 2017) - Bode, Gerrit; Behrendt, Sascha; Fütterer, Johannes; Müller, Dirk
Abstract: The expanding contribution of volatile energy sources is a challenge for the balanced and stable operation of the electrical grid. Demand side management, i.e. meaning increasing or lowering the consumption according to the supply available from renewable sources, is a viable option to stabilize grid operation. In this paper, we discuss the proposal to use the flexibility of already installed building systems. We investigated a method to identify and utilize the potential for flexible use of building energy systems and applied it to the main building of the E.ON Energy research center in Aachen, Germany.